AJARAN TAZKIYAH AL NAFS DALAM TAREKAT MUHAMMADIYAH AS SANUSIYAH AL IDRISIYAH DI KOTA MAKASSAR - Abdullah, Ahmad Hikam Muthaaliin (Bahasa Indonesia, 2024)
Study This aim For understand concepts and practices teachings tazkiyah al- nafs in the Muhammadiyah As Sanusiyah Al Idrisiyah Order in the city of Makassar, as well as evaluate its role and benefits in the lives of the followers of the congregation. Study this also delivers description about the order and its lineage. Study This is study field (field research) with use method analysis descriptive. Research result show that the Muhammadiyah As Sanusiyah Al Idrisiyah Tarekat, which is located in the sub-district Wajo, Makassar city, is a muktabarah congregation with family tree sanad that can explored to the Prophet Muhammad SAW. Draft tazkiyah al- nafs in this congregation involve practice dhikr and wirid guided by the tarekat murshid. Murshid teach importance repentance, dhikr, and prayer as part from the purification process soul. Practice dhikr and wazifa done regularly, fine in circumstances special nor in life everyday, for guard chastity heart and calm soul. Teachings tazkiyah al- nafs give impact positive, good in a way social as well as spiritual. By social, the followers of the tarekat become more tolerant, patient and moral glorious. Spiritually, they are feel more near with Allah SWT and have firm faith​ For face challenge life. Study This highlighting importance tazkiyah al- nafs in form character strong and moral individual​ good.